Effects of whey peptides on gut microbiota and food pathogens - Ya-Ju, Yu (2014)
More and more biological activities of whey peptides have been found recently, however, no relevant study has proven the potential of specific whey peptides to modulate gut microbiota, which still requires to be investigated. In the current study, whey protein concentrate (WPC) was hydrolyzed by proteases present in the Cynara cardunculus commercial extract and two fractions were generated: whey peptide extract (WPE) below 1 kDa and WPE below 3 kDa. First, WPE with molecular weight below 1 kDa was evaluated with respect to its ability to promote probiotic bacteria (Lactobacillus acidophilus and Bifidobacterium animalis) growth through microplate assay and furthermore by the determination of viable cells as well as of their metabolic activity throughout incubation time. Results illustrated that WPE 1% (w/v) had the capacity to stimulate the proliferation of both probiotic bacteria tested. Higher growth rates of L. acidophilus promoted by peptide extract were supported by the faster lactic acid production, glucose consumption and subsequent reduction on pH value, whereas in the case of B. animalis, an increase in the production of acetic acid was the main change observed. Besides the aforementioned in vitro assessments, the effect of WPE below 1 kDa on the modification of gut microbiota was also examined in the animal model using Wistar rats. By means of the quantification of 16S rRNA expression by qPCR, genera of beneficial bacteria, Lactobacillus spp. and Bifidobacterium spp. and three main phyla, Firmicutes, Bacteroidetes and Actinobacteria, as well as the indicator associated with obesity, F/B ratio were detected in fecal samples of rats. Expressions of Lactobacillus spp., Bifidobacterium spp. and Bacteroidetes were significantly elevated (p<0.05) by the intervention of WPE in the Wistar rats fed with standard diet. Consequently, the potential health-promoting effects of whey peptide extract (MW <1 kDa) were demonstrated both in vitro and in vivo. Then, we assessed the possible properties of a pure peptide (KGYGGVSLPEW), which was identified in the WPE fraction, MW <3 kDa with antihypertensive activities, but no prebiotic or antimicrobial activity has been studied until now. In order to achieve that goal, the pure peptide was synthesized chemically. In vitro studies with L. acidophilus and B. animalis were found to inhibit the growth of both probiotic bacteria, via the screening of in vitro microbroth assay. Contrarily, concerning in vivo analysis, when SD rats were fed with standard diet including this peptide, no significant change on the profile of gut microbiota caused by peptide was apparent, as concluded by results obtained from the quantification of 16S rRNA expression via qPCR, confirming the absence of deleterious effects of KGYGGVSLPEW. On the other hand, the antimicrobial activity of this peptide against two Gram-negative (Salmonella spp. and Pseudomonas aeruginosa) and two Gram-positive (Staphylococcus aureus and Listeria monocytogenes) bacteria was established through initial screening by microbroth assay. Results showed that KGYGGVSLPEW inhibited S. aureus and L. monocytogenes presenting MIC/MBC of 3% (w/v) for both bacteria, whilst it exerted a bactericidal effect on Salmonella spp. and P. aeruginosa whose MBCs were 2% in both cases. It revealed that KGYGGVSLPEW possesses antimicrobial activity against both Gram-positive and negative bacteria but underlying mechanisms are still to be enlightened. It was concluded that whey peptide extract below 1 kDa has the potential of improving gut microbiota profile, whereas synthesized pure peptide, KGYGGVSLPEW, displayed antimicrobial activity against food pathogens, showing that hydrolysis of WPC via proteases in C. cardunculus brings about these two relevant properties, resulting in an upgrade of whey, a common byproduct in cheese industry.